Violating peace : sex, aid, and peacekeeping - Westendorf, Jasmine-Kim (Cornell University Press, 2020)
"This book is about the nature of sexual exploitation and abuse by interveners in peace operations, the significant and long-term impacts it has on the capacity and credibility of the international community involved in peacekeeping, and how policies can more effectively address this phenomenon in future peace operations"--